Epidemiological Profile of Women Experiencing Domestic Violence in Brazil (Research, Society and Development, 2025)
Violence against women is a complex issue that can be analyzed from multiple perspectives, including social, biological, psychological, and epidemiological. The objective is to analyze the epidemiological profile of women in situations of intimate partner violence in Brazil over the last 10 years. Data were collected from the Notifiable Diseases Information System (SINAN), made available by the SUS Department of Informatics (DATASUS). A total of 1,974,090 cases of violence were analyzed, focusing on geographic, temporal, and sociodemographic variations. The highest incidence occurred in the Southeast region, with 4.97 cases per 1,000 people. The study revealed a substantial increase in cases, particularly in 2023. The most affected age group was women between 20 and 29 years old. In terms of race, mixed-race (Parda) women accounted for 3.83% of cases, followed by white (3.61%) and Black women (0.83%). Women of other ethnicities showed lower percentages. Regarding education, most victims had completed high school. Poisoning was the most frequent type of violence (1.93%), followed by assaults with objects. The home was the most common location, accounting for 69.66% of cases. The spouse was the perpetrator in 1.92% of incidents. The continuous rise in reports may reflect both an increase in violence and greater public awareness to report it. Given these findings, it is clear that there is a need to strengthen public policies for women's protection, invest in female empowerment, and expand support networks to ensure safe and fair conditions for women in Brazil.